Exploring knowledge and attitudes toward non-communicable diseases among village health teams in Eastern Uganda: a cross-sectional study - Temitope Tabitha Ojo; Nicola L. Hawley; Mayur M. Desai; Ann R. Akiteng; David Guwatudde; Jeremy I. Schwartz (BMC, 2017)
Abstract Background Community health workers are essential personnel in resource-limited settings. In Uganda, they are organized into Village Health Teams (VHTs) and are focused on infectious diseases and maternal-child health; however, their skills could potentially be utilized in national efforts to reduce the growing burden of non-communicable diseases (NCDs). We sought to assess the knowledge of, and attitudes toward NCDs and NCD care among VHTs in Uganda as a step toward identifying their potential role in community NCD prevention and management. Methods We administered a knowledge, attitudes and practices questionnaire to 68 VHT members from Iganga and Mayuge districts in Eastern Uganda. In addition, we conducted four focus group discussions with 33 VHT members. Discussions focused on NCD knowledge and facilitators of and barriers to incorporating NCD prevention and care into their role. A thematic qualitative analysis was conducted to identify salient themes in the data. Results VHT members possessed some knowledge and awareness of NCDs but identified a lack of knowledge about NCDs in the communities they served. They were enthusiastic about incorporating NCD care into their role and thought that they could serve as effective conduits of knowledge about NCDs to their communities if empowered through NCD education, the availability of proper reporting and referral tools, and visible collaborations with medical personnel. The lack of financial remuneration for their role did not emerge as a major barrier to providing NCD services. Conclusions Ugandan VHTs saw themselves as having the potential to play an important role in improving community awareness of NCDs as well as monitoring and referral of community members for NCD-related health issues. In order to accomplish this, they anticipated requiring context-specific and culturally adapted training as well as strong partnerships with facility-based medical personnel. A lack of financial incentivization was not identified to be a major barrier to such role expansion. Developing a role for VHTs in NCD prevention and management should be a key consideration as local and national NCD initiatives are developed.